Moderating leverage on the effect of corporate governance and profitability on firm value - Purwanti, Titik; Kuntaryanto, Oki; Utami, Tri; Marjukah, Anis; Darmawansyah, Iwan; Kalbuana, Nawang (PT WIM Solusi Prima, 2025)
This study aims to determine the effect of Corporate Governance and profitability on firm value with leverage as a moderating variable. Corporate Governance in this study is proxied by institutional ownership, public ownership, and audit committees. The population used is food and beverage companies listed on the Indonesia Stock Exchange (IDX) for 2020-2022. The sample used was 32 out of 49 food and beverage companies listed on the Indonesia Stock Exchange (IDX) for 2020-2022, with a sampling technique, namely purposive sampling or using certain considerations and criteria. The data analysis technique used is descriptive statistical analysis, classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, coefficient of determination (R2) test, t-test, and F test. The results of this study indicate that partially or simultaneously and with or without leverage as a moderating variable, the variables of institutional ownership, public ownership, audit committee, and profitability have a significant effect on firm value.